Detection of viruses in sweet potato (Ipomoea batatas L.) using qPCR - Varela-Benavides, Ingrid (2020)
Introduction. Sweet potato (Ipomoea batatas) is a root crop very susceptible to viral diseases, which have been associated with crop yield reductions of over 50 %. In the Costa Rican sweet potato plantations the presence of feathery mottle virus (SPFMV), chlorotic stunt virus (SPCSV), and leaf curl virus (SPLCV) have been reported, for the development of adequate control programs, early detection and identification is necessary through the use of sensitive and efficient techniques. Objective. The objective of this research was to estimate the incidence of SPFMV, SPCSV, and SPLCV in sweet potato plantations using qPCR. Materials and methods. In 2018 foliar tissue samples were collected from eighty plants showing viral symptoms from twenty-five sweet potato plantations distributed in four provinces in Costa Rica. The detection of the three viruses was performed by qPCR with the use of primers and specific hydrolysis probes. Results. In 92 % of the plantations studied, the presence of virosis was found. The Sweet potato virus disease (SPVD) defined as the combined infection of SPFMV and SPCSV, was the most common viral disease found in all plantations. The plantations located in Sabanilla, El Cacao, and La Guacima were the only ones to present the three viruses studied. The SPLCV virus was only detected in the Limón and Alajuela provinces. Conclusion. It is possible to make an early detection of three of the most frequent sweet potato viruses with the use of qPCR which would contribute to certified seed production programs.